Android Fat Deposition and Its Association With Cardiovascular Risk Factors in Overweight Young Males - Sari, Carolina Ika; Eikelis, Nina; Head, Geoffrey A.; Schlaich, Markus; Meikle, Peter; Lambert, Gavin; Lambert, Elisabeth (Frontiers in Physiology, 2019)
Objective Excess adiposity increases the risk of type-2 diabetes and cardiovascular disease development. Beyond the simple level of adiposity, the pattern of fat distribution may influence these risks. We sought to examine if higher android fat distribution was associated with different hemodynamic, metabolic or vascular profile compared to a lower accumulation of android fat deposits in young overweight males. Methods Forty-six participants underwent dual-energy X-ray absorptiometry and were stratified into two groups. Group 1: low level of android fat (<9.5%) and group 2: high level of android fat (>9.5%). Assessments comprised measures of plasma lipid and glucose profile, blood pressure, endothelial function [reactive hyperemia index (RHI)] and muscle sympathetic nerve activity (MSNA). Results There were no differences in weight, BMI, total body fat and lean mass between the two groups. Glucose tolerance and insulin resistance (fasting plasma insulin) were impaired in group 2 (p < 0.05). Levels of plasma triglycerides and 5 lipid species were higher in group 2 (p < 0.05). Endothelial function was less in group 2 (RHI: 1.64 vs. 2.26, p = 0.003) and heart rate was higher (76 vs. 67 bpm, p = 0.004). No difference occurred in MSNA nor blood pressure between the 2 groups. Conclusion Preferential fat accumulation in the android compartment is associated with increased cardiovascular and metabolic risk via alteration of endothelial function.